Peningkatan Hasil Belajar Peserta Didik Melalui Penggunaan Media Spinner Kata Materi Identify Taste of Different Foods and Drinks Kelas V SDN 241 Palembang - Zibrullah, Milzam; Anwar, Yenny; Dewi, Nur Fitra (Universitas Batanghari Jambi, 2025)
This research was conducted with the aim of improving students' learning outcomes in English learning with this study aiming to determine the effectiveness of the use of concrete media in the form of word spinners in improving students' learning outcomes in the English subject of Identify taste of different foods and drinks in class V.A SD Negeri 241 Palembang. The research is carried out in two cycles, with each cycle involving the stages of planning, implementation, observation, and reflection. The results of the study showed a significant improvement in student learning outcomes. In the pre-cycle, as many as 64.2% of students have not reached the Minimum Completeness Criteria (KKM), but after the implementation of interesting learning, the percentage of students who have not completed it decreased to 46.2% in the first cycle, and 17% in the second cycle. Meanwhile, the number of students who achieved KKM increased from 35.8% in the pre-cycle to 53.8% in the first cycle, and 83% in the second cycle. The conclusion of this study is that the use of concrete media in the form of word spinners is effective in improving student learning outcomes by adjusting learning according to their level of understanding and ability.